Retrofitting Homes: Cost of Mitigation Strategies for Improved Wildfire Resistance - Barrett, Kimiko; Quarles, Stephen L. (Fire and materials, 2025)
ABSTRACT As wildfire risks increase, it is essential to retrofit the existing housing stock in wildfire‐prone areas to reduce community wildfire risk. Yet there are significant questions regarding the costs and most effective strategies to retrofit homes for improved wildfire resistance. This article identifies the costs for retrofitting homes to meet the requirements specified by Chapter 7A (Materials and Construction Methods for Exterior Wildfire Exposure) in the California Building Code. Guidance from recent research related to ignition‐resistant construction was also utilized. Construction costs were calculated as a per‐unit value and were explicit to the exterior components of the home. Detailed estimates are offered for upgrading a home's exterior walls, roof, deck, windows and doors, under‐eave areas, gutters, and near‐home landscaping. Analysis demonstrates that some of the most effective strategies to reduce structure vulnerability to wildfire can be done affordably. This analysis suggested that for a typical 2000‐square‐foot home in California, retrofitting costs can be as low as $2000 for minimal retrofits to $100,000 for the highest level of protection.